2020
DOI: 10.1007/s00414-020-02368-z
|View full text |Cite
|
Sign up to set email alerts
|

Medico-legal assessment of personal damage in older people: report from a multidisciplinary consensus conference

Abstract: Ageing of the global population represents a challenge for national healthcare systems and healthcare professionals, including medico-legal experts, who assess personal damage in an increasing number of older people. Personal damage evaluation in older people is complex, and the scarcity of evidence is hindering the development of formal guidelines on the subject. The main objectives of the first multidisciplinary Consensus Conference on Medico-Legal Assessment of Personal Damage in Older People were to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Geriatric hospital patients are prone to safety incidents such as falls, fractures, lacerations, and bedsores due to impaired sensory and cognitive functions caused by various age-related chronic and degenerative diseases such as high blood pressure, diabetes, dementia, Parkinson’s disease, cardiovascular disease, stroke, hearing and visual impairment, and senile depression [ 8 ]. When safety incidents occur, elderly patients with multiple comorbidities are more likely to experience worse outcomes in terms of mortality, complications, and quality of life compared to younger patients [ 9 ]. For this reason, elderly patients’ safety incidents not only directly affect their lives but also degrade the quality of healthcare services due to prolonged hospitalizations and increased inpatient costs.…”
Section: Introductionmentioning
confidence: 99%
“…Geriatric hospital patients are prone to safety incidents such as falls, fractures, lacerations, and bedsores due to impaired sensory and cognitive functions caused by various age-related chronic and degenerative diseases such as high blood pressure, diabetes, dementia, Parkinson’s disease, cardiovascular disease, stroke, hearing and visual impairment, and senile depression [ 8 ]. When safety incidents occur, elderly patients with multiple comorbidities are more likely to experience worse outcomes in terms of mortality, complications, and quality of life compared to younger patients [ 9 ]. For this reason, elderly patients’ safety incidents not only directly affect their lives but also degrade the quality of healthcare services due to prolonged hospitalizations and increased inpatient costs.…”
Section: Introductionmentioning
confidence: 99%
“…Last, the study did not assess the benefits of subjects who received support from volunteer activities. To further examine the useful of volunteer activity and to promote the volunteer activity in elderly, the multidimensional assessment [ 28 ] should be used in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a multidisciplinary consensus from Italy pointed out the potentially negative impact of old age on recovery of patients from damage. The consensus also put forward some useful evaluation benchmarks for the elderly before operation, which would be critical for the selection of the elderly patients for surgery in the future [21]. Although some previous literature reported that older patients had similar surgical safety and long-term survival compared with younger patients, baseline data for both groups were not balanced.…”
Section: Discussionmentioning
confidence: 99%